Enhancing MIDAS towards a transparent interoperability between SaaS and DaaS - Vieira, Marcelo; Ribeiro, Elivaldo; Rocha, Witã; Mane, Babacar; Claro, Daniela; Oliveira, Joevan; Lima, Edmilson (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2017: Anais do XIII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2017.6062, 2017)
Over the years, Software as a Service (SaaS) has become a common delivery model for many applications. In cloud applications, a huge volume and variety of data can be generated and they can be available for consumption by DaaS (Data as a Service). For this, the data provided by DaaS can be stored in a non-structured (e.g. text), semi-structured (e.g. XML, JSON) or structured format (e.g. Relational Database). However, the access of that kind of DaaS, in a transparent manner, needs substantial efforts due to the lack of interoperability between SaaS and DaaS. In this paper, we propose a new enhanced version of MIDAS, middleware to provide seamlessly and independently interoperability between SaaS and DaaS. First, this new version of MIDAS allows both semi-structure and structure data format from SaaS. It mediates queries from NoSQL (e.g. MongoDB) and SQL (MySQL) databases. Secondly, it was enhanced with Join operations, both in SQL and in NOSQL statements. And lastly, other formats were added for the DaaS to fit SaaS requests, such as JSON, XML, and CSV formats. To evaluate this new version of our middleware, we provide three types of experiments to cover critical issues such as execution time, the overhead of our approach, and scalability of MIDAS. Our results show the effectiveness of our approach to tackling interoperability issues in cloud computing environments.